Uncertainty analysis of a large break loss of coolant accident in a pressurized water reactor using non-parametric methods. (June 2018) - Sanchez-Saez, F.; Sánchez, A.I.; Villanueva, J.F.; Carlos, S.; Martorell, S.
Highlights: A BEPU analysis in a LBLOCA with non-parametric methods is proposed. In order to compare the methods, performance metrics are employed. Wilks' method is compared with Beran–Hall, Hutson and Bootstrap techniques. Abstract: The safety analysis of nuclear power plant is moving toward a realistic approach in which the simulations performed using best estimate computer codes must be accompanied by an uncertainty analysis, known as the Best Estimate Plus Uncertainties approach. The most popular statistical method used in these analyses is the Wilks' method, which is based on the principle of order statistics for determining a certain coverage of the Figures-of-Merit with an appropriate degree of confidence. However, there exist other statistical techniques that could provide similar or even better results. This paper explores the performance of alternative non-parametric methods as compared to the Wilks' method of obtaining such Figure-of-Merits tolerance intervals. Three methods are investigated, i.e. Hutson and Beran–Hall methods and a bootstrap method. All the techniques have been used to perform the uncertainty analysis of a Large-Break Loss of Coolant Accident. The Figure-of-Merit of interest in this application is the maximum value reached by the Peaking Clad Temperature. In order to analyze the results obtained by the different methods, four performance metrics are proposed to measure the coverage, dispersion, conservativeness, and robustness of the tolerance intervals.